Cardiorespiratory Fitness Analysis Based on Sex and Age Among Students at SMK Bina Nusantara Ungaran - Mohammad Ibnu Aldi; Wiga Nurlatifa Romadhoni; Ana Nurlatifah (Journal of Sport Science and Fitness, 2026)
Background: cardiovascular and respiratory fitness (CRF) is a critical health indicator linked to students metabolic well being and funcional capacity to perform physical activities. Despite its importance, empirical evidence regarding the distribution of maximum oxygen consumption (VO2MAX), particularly among vocational high school students, remains limited. Objectives: the purpose of this study is to analyze the descriptive statistical profile and categorical distribution of vo2max among students at smk bina nusantara ungaran, grouped by age and biological sex. Method: this study employed a quantitative descriptive design involving 298 students (223 males and 75 famales). Vo2max was measured using the 1.6km rockport walk test, and the data were analyzed using descriptive statistics, including mean, standard deviation, and frequency distribution. Result: the resuts of the study showed that male students achived an average vo2max value of 35.02 ± 5.07 ml/kg/min, while female students showed a lower average value of 27.35 ± 3.10 ml/kg/min. Specifically, categorical analysis revealed a significant fitness gap, with 32.73% of male students and 70.66% of female students falling into the into the poor and very poor categories. Conclusion: in conclusion, the majority of students, particularly female students, exhibit suboptimal levels of cardiovascular and respiratory fitness, wjich may affect their readines to enter the workforce in the future. These findings underscore the urgent need for gender inclosive physical activity interventions and policy adjustments in vocational education to improve long term health and industrial productivity.